Discerning the Surface and Bulk Recombination Kinetics of Organic–Inorganic Halide Perovskite Single Crystals. Issue 14 (27th May 2016) - Wu, Bo; Nguyen, Huy Tiep; Ku, Zhiliang; Han, Guifang; Giovanni, David; Mathews, Nripan; Fan, Hong Jin; Sum, Tze Chien
Abstract : Organic–inorganic halide perovskite single crystals possess many outstanding properties conducive for photovoltaic and optoelectronic applications. However, a clear photophysics picture is still elusive, particularly, their surface and bulk photophysics are inexorably convoluted by the spectral absorbance, defects, coexisting photoexcited species, etc. In this work, an all‐optical study is presented that clearly distinguishes the surface kinetics from those of the bulk in the representative methylammonium‐lead bromide (MAPbBr3 ) and ‐lead iodide (MAPbI3 ) single crystals. It is found that the bulk recombination lifetime of the MAPbBr3 single crystal is shortened significantly by approximately one to two orders (i.e., from ≈34 to ≈1 ns) at the surface with a surface recombination velocity of around 6.7 × 10 3 cm s −1 . The surface trap density is estimated to be around 6.0 × 10 17 cm −3, which is two orders larger than that of the bulk (5.8 × 10 15 cm −3 ). Correspondingly, the diffusion length of the surface excited species is ≈130–160 nm, which is considerably reduced compared to the bulk value of ≈2.6–4.3 μm. Furthermore, the surface region has a wider bandgap that possibly arises from the strong lattice deformation. The findings provide new insights into the intrinsic photophysics essential for single crystal perovskite photovoltaics and optoelectronic devices. Abstract : The surface and bulk photophysics of perovskite single crystals are clearly separated in an all‐optical approach. Their surface photophysics is similar to that of polycrystalline thin films, but is significantly different in the bulk region. Key properties from both regions (e.g., recombination lifetimes, trap densities, surface recombination velocity, diffusion lengths, etc.) essential for optoelectronic applications are obtained in this comprehensive study.